Management of fortuity: Workplace chance events and the career projections of up-or-out professionals - Barbulescu, Roxana; Jonczyk Sédès, Claudia; Galunic, Charles; Bensaou, Ben (My University, 2022)
How much control do people have over their career? We explore this question in the context of professional service firms, long thought of as providing predictable, agentic careers in the up-orout model. Specifically, we seek to understand how chance events in immediate work circumstances are experienced in this context, and the responses they elicit in terms of career construction. Drawing on in-depth interviews with 68 pre-partnership professionals from three large professional firms using the up-or-out promotion system, we find that chance developments in proximate work conditions, especially with respect to key relationships and project allocation, shape the possibilities that professionals see for their careers going forward and the actions they take in response. Even in this seemingly predictable career, being continuously attuned to fortuitous turns of events informs how people enact career agency. It also prompts a heightened awareness of the fragile nature of the up-or-out career path, triggering a gradual reconsideration of career possibilities that includes career confirmation, ambivalence, pivot, and fading. Our study contributes to better understanding the interdependence between context and agency in contemporary careers, highlighting the widespread and consequential role of proximate chance events in people’s career construction process.
Keywords: Careers Chance events Agency Structure Professional service firms Up-or-out